Mobility for learners and staff - higher education students and staff mobility inter-institutional agreement 2019-2021 between programme countries - Universidade Lusíada de Lisboa and Universidad Rey Juan Carlos - Universidade Lusíada de Lisboa (2020)
- Cooperate for exchange of students and/or staff in the context of the Erasmus + programme; - Subject area: Industrial organization engineering.